2 x − 6 y + z = − 1 2 ...............(1)
3 x + 5 y − 3 z = − 1 7 .............. (2)
− 4 x − y + 2 z = 2 2 ............... (3)
Three equations are given above, what is the value of x − y + z ?
Try this: All of my problems
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Given that,
2 x − 6 y + z = − 1 2 .............(1)
3 x + 5 y − 3 z = − 1 7 ............(2)
− 4 x − y + 2 z = 2 2 ..............(3)
Now, Multiply equation (1) by 3 and equation (2) by 1.
6 x − 1 8 y + 3 z = − 3 6 ........(4)
3 x + 5 y − 3 z = − 1 7 .........(2)
Add equations (4) and (2).
9 x − 1 3 y = − 5 3 ................(5)
Multiply equation (1) by 2 and equation (3) by 1.
4 x − 1 2 y + 2 z = − 2 4 ..............(6)
− 4 x − y + 2 z = 2 2 ....................(3)
Subtract equation (3) from equation (6).
8 x − 1 1 y = − 4 6 .......(7)
Multiply equation (5) by 8 and equation (7) by 9.
7 2 x − 1 0 4 y = − 4 2 4 .........(8)
7 2 x − 9 9 y = − 4 1 4 ...........(9)
Subtract equation (9) from equation (8).
− 5 y = − 1 0 ⇒ y = 2
Now we have the value of y ,
Substitute it back into equation (7) to find x .
⇒ 8 x − 2 2 = − 4 6 ⇒ 8 x = − 2 4 ⇒ x = − 3
Now we have the values of y and x .
Substitute them back into equation (1) to find z
⇒ − 6 − 1 2 + z = − 1 2 ⇒ z = 6
Therefore, ⇒ x − y + z = − 3 − 2 + 6 = 1 .
Problem Loading...
Note Loading...
Set Loading...
2 x − 6 y + z = − 1 2 ( 1 )
3 x + 5 y − 3 z = − 1 7 ( 2 )
− 4 x − y + 2 z = 2 2 ( 3 )
I will eliminate x from ( 1 ) and ( 2 ) . Then I will eliminate x again from ( 2 ) and ( 3 ) .
{ ( 1 ) × − 3 } + { ( 2 ) × 2 } ⟹ 2 8 y − 9 z = 2 ( 4 )
{ ( 2 ) × 4 } + { ( 3 ) × 3 } ⟹ 1 7 y − 6 z = − 2 ( 5 )
Now I will eliminate z from ( 4 ) and ( 5 ) to solve for y .
{ ( 4 ) × − 6 } + { ( 5 ) × 9 } ⟹ y = 2
Substitute y = 2 in ( 4 ) to solve for z
2 8 ( 2 ) − 9 z = 2
5 6 − 2 = 9 z
5 4 = 9 z
6 = z
Substitute z = 6 and y = 2 in ( 1 ) to solve for x .
2 x − 6 ( 2 ) + 1 6 = − 1 2
2 x = − 1 2 + 1 2 − 6
2 x = − 6
x = − 3
Finally,
x − y + z = − 3 − 2 + 6 = 1